Enduring effects of psychotherapy, antidepressants and their combination for depression: a systematic review and meta-analysis - Voderholzer, Ulrich; Barton, Barbara B.; Favreau, Matthias; Zisler, Eva M.; Rief, Winfried; Wilhelm, Marcel; Schramm, Elisabeth (Frontiers in Psychiatry, 2024)
IntroductionAlthough depressive disorders are frequently associated with relapses, the sustained efficacy of therapies after their termination has been insufficiently investigated.ObjectiveThe aim of this study was to evaluate the current evidence of enduring effects of psychotherapy, antidepressants and their combination after the end of treatment.MethodsPubMed and PsychINFO were systematically screened according to PRISMA guidelines (except for preregistration). Only randomized controlled trials (RCTs) between 1980 and 2022 comparing the efficacy of psychotherapy, antidepressants and their combination in adult depression at follow-up at least 12 months after termination of therapy, which could be acute phase, maintenance or relapse prevention therapy, were included. Risk of bias was assessed by using the Cochrane risk of bias tool.ResultsIn total 19 RCTs with a total of 1154 participants were included. Psychotherapy was significantly superior to pharmacotherapy regarding relapse rates and Beck Depression Inventory scores at follow-up after acute treatment in two of nine RCTs. Combined treatment performed significantly better than pharmacotherapy, but not psychotherapy, regarding relapse and remission in five out of nine RCTs at least 12 months after treatment termination. Pairwise meta-analyses indicated a superiority of combined treatment compared to pharmacotherapy alone regarding relapse, recurrence, and rehospitalization rates (RR=0.60, 95%-CI: 0.37-0.97, p=.041) and for psychotherapy compared to pharmacotherapy alone regarding relapse and recurrence rates (RR=0.58, 95%-CI: 0.38-0.89, p=.023), however comparative treatment effects between psychotherapy and combined treatment were insignificant.ConclusionsCurrent findings suggest a superiority of psychotherapy and combined treatment over pharmacotherapy alone in major depressive disorder depression. Major limitations were a low number of studies reporting follow-up data after termination of study periods and a heterogeneity in definitions of treatment outcomes. Practice guidelines and participatory decision-making processes for the choice of treatment should consider the current knowledge on long-term effects of antidepressant therapy methods more than has been the case to date.